IMPLEMENTASI MULTIMEDIA SYAIR LAGU DAERAH SEBAGAI UPAYA PENINGKATAN MOTIVASI DAN PEMAHAMAN SISWA PADA PEMBELAJARAN MATEMATIKA KELAS 1 SD NEGERI MUNTILAN - Chodariyah, Dwi Enik Nuzul; Moh. Rusnoto Susanto; Sukiyanto, Sukiyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Mathematics and SBDP (Social and Cultural Arts and Physical Education) are mandatory subjects in Elementary School. From grade 1 to grade 6, these subjects are taught. So far, Mathematics is considered a difficult subject, causing many students to be uninterested in it. This lack of interest results in a low motivation to attend Mathematics lessons. Given this phenomenon, it is necessary to create engaging lessons for students. These lessons can be integrated with other subjects and also related to P5 (Project for Strengthening Pancasila Student Profiles), in line with the Merdeka Belajar curriculum. Projects with cultural values, themed on local wisdom, are ideal. Additionally, in this digital age, we must be able to implement multimedia learning to facilitate the delivery of lesson materials to students. This study aims to evaluate the effectiveness of implementing multimedia based on local song lyrics in increasing the motivation and understanding of first-grade students at SD Negeri Muntilan in Mathematics. The background of this research is the low interest of students in Mathematics, which is often considered difficult and boring. The number of research subjects is 27 first-grade students at SD Negeri Muntilan who show a lack of motivation and understanding in Mathematics. This research uses a quantitative approach with an experimental design. The experimental group received Mathematics lessons through multimedia based on local song lyrics, while the control group received lessons using conventional methods. Data were collected through Mathematics comprehension tests and learning motivation questionnaires before and after the intervention. The results of the study show that the use of multimedia based on local song lyrics significantly increases students' motivation and understanding of Mathematics. The average Mathematics comprehension scores of the students increased by 23%, while their learning motivation increased by 28%. These findings indicate that this innovative approach is effective in changing students' perceptions of Mathematics and improving their learning outcomes. The conclusion of this study is that the implementation of multimedia based on local song lyrics can be an effective strategy in increasing students' motivation and understanding of Mathematics in first-grade elementary school. The integration of local culture in learning not only helps preserve cultural heritage but also makes the learning process more engaging and enjoyable for students.